Leukocyte Telomere Length and Cognitive Function in Older Adults - Emily Frith; Paul D. Loprinzi (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
We evaluated the specific association between leukocyte telomere length and cognitive function among a national sample of the broader U.S. older adult population. Data from the 1999-2002 National Health and Nutrition Examination Survey (NHANES) were used to identify 1,722 adults, between 60-85 years, with complete data on selected study variables. DNA was extracted from whole blood via the LTL assay, which is administered using quantitative polymerase chain reaction to measure telomere length relative to standard reference DNA (T/S ratio). Average telomere length was recorded, with two to three assays performed to control for individual variability. The DSST (Digit Symbol Substitution Test) was used to assess participant executive cognitive functioning tasks of pairing and free recall. Individuals were excluded if they had been diagnosed with coronary artery disease, congestive heart failure, heart attack or stroke at the baseline assessment. Leukocyte telomere length was associated with higher cognitive performance, independent of gender, race-ethnicity, physical activity status, body mass index and other covariates. In this sample, there was a strong association between LTL and cognition; for every 1 T/S ratio increase in LTL, there was a corresponding 9.9 unit increase in the DSST (β = 9.9; 95% CI: 5.6-14.2; P [JCBPR 2018; 7(1.000): 14-18]